1992
DOI: 10.1111/j.1432-1033.1992.tb17405.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β and transforming growth factor‐β2 enhance cytosolic high‐molecular‐mass phospholipase A2 activity and induce prostaglandin E2 formation in rat mesangial cells

Abstract: Interleukin-1P induces gene expression and secretion of group-I1 phospholipase A, and release of prostaglandin E2 from rat mesangial cells. The interleukin-lp-induced synthesis of group-I1 phospholipase A2 is prevented by transforming growth factor-/?,, whereas transforming growth factor-p2 potentiated the interleukin-lp-evoked prostaglandin E, production. Transforming growth factor-p, itself did not induce synthesis of group-I1 phospholipase A,, although it stimulated prostaglandin E2 formation. Here we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 50 publications
0
39
1
Order By: Relevance
“…Interestingly, the expression of sPLA 2 -IIA induced by TNF␣ was only weakly reduced by pyrrolidine-1, although proinflammatory cytokines are known to produce a delayed activation of cPLA 2 in rat mesangial cells (51,52). This suggests that the delayed activation of cPLA 2 is not a major route in the TNF␣ signaling pathway leading to sPLA 2 -IIA expression.…”
Section: Role Of Heparan Sulfate Proteoglycans In Splamentioning
confidence: 77%
See 1 more Smart Citation
“…Interestingly, the expression of sPLA 2 -IIA induced by TNF␣ was only weakly reduced by pyrrolidine-1, although proinflammatory cytokines are known to produce a delayed activation of cPLA 2 in rat mesangial cells (51,52). This suggests that the delayed activation of cPLA 2 is not a major route in the TNF␣ signaling pathway leading to sPLA 2 -IIA expression.…”
Section: Role Of Heparan Sulfate Proteoglycans In Splamentioning
confidence: 77%
“…In this regard, cytokines differ significantly and cause a delayed increase in cPLA 2 by up-regulating its mRNA expression (51,52). To elucidate whether cPLA 2 activation is involved in sPLA 2 -IIA expression, we analyzed the effect of pyrrolidine-1, a recently characterized specific inhibitor of cPLA 2 ␣ (53, 54).…”
Section: Exogenous Spla 2 S Induce Spla 2 -Iia Expression Via Ppar␣ Amentioning
confidence: 99%
“…sion was also documented in certain cytokine-treated cells (Schalkwijk et al, 1992, Nakamura et al, 1992Lin et al, 1992b). It was reported previously that cPLA, prepared from the mouse macrophage-like cell line, RAW264.7, apparently exhibited both phospholipase A, and lysophospholipase activities (Leslie, 1991), although the activity of phospholipase A, was about 10% that of phospholipase A,.…”
mentioning
confidence: 99%
“…Agonists, such as thrombin, platelet-derived growth factor, epidermal growth factor and ATP [16][17][18], plus the serine kinases protein kinase C (PKC) and mitogen-activated protein (MAP) kinase, were shown to phosphorylate and activate cPLA z [19,20]. Furthermore, it has been shown that cytokines, macrophage colony-stimulating factor can influence cPLA2 activity [21][22][23]. Cytokines, such as interleukin-lfl and *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%